Effectiveness Of Ventilatory Support Implementation To Address Ineffective Breathing Patterns In Children With Anaphylactic Shock Diagnosis At Porsea Regional General Hospital - Minar Lenny Situmorang; Rifka Banjarnahor; Natasya Sihombing (International Journal of Health Engineering and Technology, 2026)
Effectiveness of implementing ventilation support to address inefective breathing patterns with a diagnosis o anaphylactive shock in the room porsea regional hospital toba. Anaphylactic shock is an allergic reaction that can cause loss of consciousness or even death, this condition occurs when the patient is allergic to food, drugs, insect venom. This scientific objective aims to reduce ineffective breathing patterns by implementing nursing with the application of ventilation support in hospitals with anaphylactic shock.  The method used to conduct Nursing Care is by approaching through data collection, analyzing data, and drawing conclusions.  The results of this study show that the application of ventilation support can have an effect on overcoming ineffective breathing patterns in anaphylactic shock patients. So the conclusion of Nursing Care given to clients during the three days of treatment application of ventilation support can have an influence on reducing ineffective breathing patterns namely reduced tightness and breathing back to stable. It is recommended to give the family a semi-fowler position and use loose clothes if there is tightness in the child.